Stictonectes rebeccae sp. n. from the Iberian Peninsula, with notes on its phylogenetic position (Coleoptera, Dytiscidae) - Bilton, David T. (Zootaxa, 2012)
Stictonetes rebeccae sp. n. (Coleoptera, Dytiscidae) is described from central and northwestern Iberia. The new species isclose morphologically to Stictonectes epipleuricus (Seidlitz, 1887), widespread in Iberia and adjacent areas of southernFrance, and Stictonectes occidentalis Fresneda & Fery, 1990, endemic to the extreme southwest of Portugal and Spain.Characters on which the three species can be distinguished are presented and discussed; the apex of the male parameresbeing particularly diagnostic. A molecular phylogeny based on fragments of two mitochondrial genes places S. rebeccaesp.n. sister to S. occidentalis. These two taxa are entirely allopatric, and according to molecular clock estimations divergedduring the late Pleistocene. S. rebeccae sp. n. is broadly sympatric with S. epipleuricus, although to date the two taxa havenot been collected in the same localities. A lectotype of S. epipleuricus is designated from the collection in the Zoologische Staatssammlung, Munich.